2012
DOI: 10.1063/1.3684964
|View full text |Cite
|
Sign up to set email alerts
|

Faster radial strain relaxation in InAs–GaAs core–shell heterowires

Abstract: The structure of wurtzite and zinc blende InAs–GaAs (001) core–shell nanowires grown by molecular beam epitaxy on GaAs (001) substrates has been investigated by transmission electron microscopy. Heterowires with InAs core radii exceeding 11 nm, strain relax through the generation of misfit dislocations, given a GaAs shell thickness greater than 2.5 nm. Strain relaxation is larger in radial directions than axial, particularly for shell thicknesses greater than 5.0 nm, consistent with molecular statics calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 29 publications
4
48
0
Order By: Relevance
“…3 Therefore, there have been significant efforts in the past few years to achieve axial and radial heterostructure NWs. Among III-V heterostructure NWs, InAs/GaAs, 4 GaP/GaAs, 5 and GaAs/GaIn 1Àx P x (Ref. 6) core/shell NWs and GaAs/GaSb (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…3 Therefore, there have been significant efforts in the past few years to achieve axial and radial heterostructure NWs. Among III-V heterostructure NWs, InAs/GaAs, 4 GaP/GaAs, 5 and GaAs/GaIn 1Àx P x (Ref. 6) core/shell NWs and GaAs/GaSb (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…20 In fact, there have been reports on strain relaxation through defect formations in other NP radial heterostructures for shell thicknesses more than several times the bulk critical thickness. 21,22 In our InAs/InP NPs, however, no strain relaxation is observed by TEM or diffraction pattern. This is likely because the InP shell is still within the coherency limits for such radial NP heterostructure, which is reported to be higher than that of planar.…”
mentioning
confidence: 73%
“…For example, it was theoretically shown that misfit strains in the core-shell and embedded nanowires can relax by straight misfit edge [12][13][14][15] and screw [16] dislocations, misfit wedge disclinations and dislocation walls [17], prismatic [14,15,[18][19][20][21] and glide [22] dislocation loops, and penny-shape cracks [21]. Experimental evidence of misfit dislocations was demonstrated in GaP-GaN [23], Ge-Si [24], AlN-GaN [25], and InAs-GaAs [26][27][28] core-shell nanowires.…”
Section: Introductionmentioning
confidence: 97%